2021
DOI: 10.18502/jthc.v16i1.6597
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Embolism and Right Heart Thrombi: A Single-Center Experience

Abstract: Background: The right heart thrombus (RHT) embolizes from deep venous thrombi and sits in the right atrium or the right ventricle. We aimed to determine the occurrence and prognosis of the RHT in patients with pulmonary embolism. Methods: We reviewed the cohort data of 622 patients with acute pulmonary embolism obtained from the registry of Tehran Heart Center. Demographic, physiological, clinical, and echocardiographic data, as well as clinical outcomes, were compared between patients with and without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…The risk factors for RHT also varied in different studies. Previous studies reported that RHT‐APE patients had lower SBP, 4 , 6 higher APE risk stratification, 6 higher proportion of RV hypokinesis, 4 , 5 , 6 , 14 and higher BNP levels, 6 which were in consistence with our study. Besides, the present study also reported that RHT patients had younger age, 6 higher proportion of male gender, 15 and higher levels of creatinine, 6 which were also in line with others' studies.…”
Section: Discussionsupporting
confidence: 92%
“…The risk factors for RHT also varied in different studies. Previous studies reported that RHT‐APE patients had lower SBP, 4 , 6 higher APE risk stratification, 6 higher proportion of RV hypokinesis, 4 , 5 , 6 , 14 and higher BNP levels, 6 which were in consistence with our study. Besides, the present study also reported that RHT patients had younger age, 6 higher proportion of male gender, 15 and higher levels of creatinine, 6 which were also in line with others' studies.…”
Section: Discussionsupporting
confidence: 92%
“…In the same manner, the loss of the corresponding right ventricle contribution to the preloading of the left ventricle in AF can aggravate hemodynamic disturbances in patients with PE [24,25]. In particular, in patients with permanent AF, the thrombotic embolus may originate from the right atrium [26,27]. AF promotes a pro-thrombotic state by inducing the production of platelets and coagulation cascades, which can lead to thrombosis and eventual PE.…”
Section: Discussionmentioning
confidence: 99%